Recalibrate: changing paradigms - Singh, N. K. (New Delhi Rupa, 2022)
This book seeks to tackle emerging challenges in fiscal federalism and policy, governance reforms, the future of agriculture, disaster risk management, technology.
Keywords: Geopolitics